Importance of drying to control internal curing effects on field casting ultra-high performance concrete. (June 2018) - Kang, Sung-Hoon; Hong, Sung-Gul; Moon, Juhyuk
Abstract: In this study, the interdependent relationships among hydration reaction, internal relative humidity (RH), and strength of internally cured ultra-high performance concrete (UHPC) were investigated, to emphasize the importance of drying on superabsorbent polymer-based internal curing (IC). Experiments showed that the self-desiccation of UHPC cannot be prevented by external curing, such as water curing, but can be prevented by IC. Although the desiccation and resulting shrinkage of UHPC were effectively mitigated by the IC, a slow strength development was found when maintaining a high internal RH. Under water-curing conditions, the internally cured UHPCs showed 12–17% lower strength at 28 days compared with the reference sample. However, the results were 0–1% when exposed to dry air (RH 60%) between 7 and 28 days, showing accelerated external drying. The results show that the early-age shrinkage-related problem of UHPC can be fundamentally resolved, without a negative effect on strength, by controlling the drying period.